Accuracy of navigation guided implant surgery for immediate loading complete arch restorations: Prospective clinical trial - Pozzi, Alessandro; Carosi, Paolo; Laureti, Andrea; Mattheos, Nikos; Pimkhaokham, Atiphan; Chow, James; Arcuri, Lorenzo (CLINICAL IMPLANT DENTISTRY AND RELATED RESEARCH, 2024)
Objectives To assess navigation accuracy for complete‐arch implant placement with immediate loading of digitally prefabricated provisional. Materials and Methods Consecutive edentulous and terminal dentition patients requiring at least one complete‐arch FDP were treated between December 2020 and January 2022. Accuracy was evaluated by superimposing pre‐operative and post‐operative cone beam computed tomography (CBCT), recording linear (mm) and angular (degrees) deviations. T‐tests were performed to investigate the potential effect of the registration algorithm (fiducial‐based vs. fiducial‐free), type of references for the fiducial‐free algorithm (teeth vs. bone screws), site characteristic (healed vs. post‐extractive), implant angulation (axial vs. tilted), type of arch (maxilla vs. mandible) on the accuracy with p‐value <0.05. Results Twenty‐five patients, 36 complete‐arches, and 161 implants were placed. The overall mean angular deviation was 2.19° (SD 1.26°). The global platform and apex mean deviations were 1.17 mm (SD 0.57 mm), and 1.30 mm (SD 0.62 mm). Meaningful global platform (p = 0.0009) and apical (p = 0.0109) deviations were experienced only between healed and post‐extraction sites. None of the analyzed variables significantly influenced angular deviation. Minor single‐axis deviations were reported for the type of jaw (y‐axis at implant platform and apex), registration algorithm (y‐axis platform and z‐axis deviations), and type of references for the fiducial‐free algorithm. No statistically significant differences were found in relation to implant angulation. Conclusions Within the study limitations navigation was reliable for complete‐arch implant placement with immediate loading digitally pre‐fabricated FDP. AI‐driven surface anatomy identification and calibration protocol made fiducial‐free registration as accurate as fiducial‐based, teeth and bone screws equal as references. Implant site characteristics were the only statistically significant variable with healed sites reporting higher accuracy compared to post‐extractive. Live‐tracked navigation surgery enhanced operator performance and accuracy regardless of implant angulation and type of jaw. A mean safety room of about 1 mm and 2° should be considered.